Ocena inwestycji gospodarstw rolnych w środki mechanizacji - Bojar, Waldemar (Evaluation of Farm Equipment Investment, 2005)
In the paper investment processes concerning farm machinery modernisation in Polish family farms located in Kujawy and Pomorze province between 1998 and 2003 are presented. One can observe essential growth in number of tractors, aggregates, sprayers and other types of machinery agreed with more intensive and specialised production. At the same time, a number of newly purchased machinery was limited because of a shortage of capital means. One can underline that total draught power was increased but unit draught power per one hectare was decreased what is a positive phenomenon in adjustment processes of domestic farms in Poland. Observed changes create perspectives for improvement of effects of work and production. Chances for acceleration of farm equipment modernisation creates inflow of expected EU funds.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 65-69